A bispecific antibody agonist of the IL-2 heterodimeric receptor preferentially promotes in vivo expansion of CD8 and NK cells - Harris, Katherine E. (Sci Rep, 2021)
The use of recombinant interleukin-2 (IL-2) as a therapeutic protein has been limited by significant toxicities despite its demonstrated ability to induce durable tumor-regression in cancer patients. The adverse events and limited efficacy of IL-2 treatment are due to the preferential binding of IL-2 to cells that express the high-affinity, trimeric receptor, IL-2Rαβγ such as endothelial cells and T-regulatory cells, respectively. Here, we describe a novel bispecific heavy-chain only antibody which binds to and activates signaling through the heterodimeric IL-2Rβγ receptor complex that is expressed on resting T-cells and NK cells. By avoiding binding to IL-2Rα, this molecule circumvents the preferential T-reg activation of native IL-2, while maintaining the robust stimulatory effects on T-cells and NK-cells in vitro. In vivo studies in both mice and cynomolgus monkeys confirm the molecule’s in vivo biological activity, extended pharmacodynamics due to the Fc portion of the molecule, and enhanced safety profile. Together, these results demonstrate that the bispecific antibody is a safe and effective IL-2R agonist that harnesses the benefits of the IL-2 signaling pathway as a potential anti-cancer therapy.